2018
DOI: 10.1039/c8cc05073b
|View full text |Cite
|
Sign up to set email alerts
|

Chiral phosphoric acid catalyzed enantioselective N-alkylation of indoles with in situ generated cyclic N-acyl ketimines

Abstract: A chiral SPINOL derived phosphoric acid-catalyzed asymmetric N-alkylation reaction of indoles with cyclic α-diaryl-substituted N-acyl imines, which are generated in situ from 3-aryl 3-hydroxyisoindolinones, has been demonstrated. The transformation proceeds smoothly with a broad range of indoles and isoindolinone alcohols. A variety of indole derived N-alkylated tetrasubstituted chiral aminals were afforded in moderate to good yields (50-79%) with excellent enantioselectivities (up to 98% ee).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…To gain the insight of the reaction mechanism, several control experiments were carried out (Scheme ). The N ‐methylated 3‐hydroxyisoindolinone 8 , which is believed unable to undergo dehydration upon treatment with chiral phosphoric acids, was found to be unreactive under the established reaction conditions (Scheme a). This result showed that the formation of cyclic ketimine intermediates is crucial for this reaction.…”
Section: Methodsmentioning
confidence: 99%
“…To gain the insight of the reaction mechanism, several control experiments were carried out (Scheme ). The N ‐methylated 3‐hydroxyisoindolinone 8 , which is believed unable to undergo dehydration upon treatment with chiral phosphoric acids, was found to be unreactive under the established reaction conditions (Scheme a). This result showed that the formation of cyclic ketimine intermediates is crucial for this reaction.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, Zeng and Zhong in 2018 reported an asymmetric N-alkylation of indoles with in situ generated αdiaryl-substituted N-acyl ketimines from 3-aryl-3hydroxyisoindolinones catalyzed by chiral SPINOL derived phosphoric acid 13 b (Scheme 27). [11] The N-alkylated indoles 85 were selectively furnished in moderate to good yields (50-79%) and excellent ee values (up to 98% ee). Control experiment using N-methyl indole gave only the C2-alkylation product with no ee value.…”
Section: Nitrogen-based Nucleophilesmentioning
confidence: 98%
“…Interestingly, Boc and phenyl N-protected α,β-unsaturated γ-lactams afforded only C3 alkylated products with low ee values. Another example of the application of SPINOL-derived phosphoric acid in the N-alkylation of indoles was demonstrated by Zeng and Zhong [25]. An enantioselective N-addition of indoles to in situ generated cyclic N-acyl imines from hydroxy isoindolinones 23 was efficiently catalyzed by hindered bismesityl-substituted chiral phosphoric acid 25 (Scheme 9).…”
Section: N-selective Additions Of Indoles To Imine/iminium Activated mentioning
confidence: 99%